Using Secure Virtual Private Networks for Increasing the Patient Privacy in the case of Telemonitoring Services - GBEDANDE, Jules; DOSSOU, MICHEL; VIANOU, COKOU ANTOINE; YATAKPO, Henoc; ASSOGBA, Kokou Marc (My University, 2019)
Global health care system is facing a crucial personnel shortage issue. Developing countries bear the high shortage burden. This is due to mass brain drain from developing to developed countries. Remote health care systems aim at increasing access to health care for outpatient living at remote areas where access to health care services represents a challenge. Homecare also takes benefit from remote health care. Sharing information in the remote health care system can be done via virtual private networks (VPN). Virtual Private Networks (VPN) permit to share information through secure tunnel on internet. However, VPN faced some security issues such as Distributed Denial of Service (DDoS), identity theft attacks… The goal of this article is to enhance VPN security by providing a firewall-based system and Snort-inline intrusion prevention system.
Keywords: Intrusion; VPN; Snort-inline; Tunnel; Attacks